10 c’s of social networking, interconnections and the impact on social networking - Shah, Asadullah; Shaikh, Muniba (2013)
Social networking is unquestionably one of the most vital and influential aspect of today’s society. Social networking has been in use in various forms such as prodigy an interactive personal service, GEnie and CompuServe are known to be the early social networks. This paper provides an analysis of facebook, LinkedIn, Twitter and MySpace, all current, interactive social networks. The data has been collected from secondary sources. The data has been analyzed and compared for its user base and growth since their existence and also gender base users for various age groups. The analysis of data indicate some useful and new insights such as, the facebook is the most popular network having the highest number of users. LinkedIn network, in the age groups between 34 to 45 years having the highest number of users. Interestingly LinkedIn, in gender base analysis, for the age groups of 34-45 numbered less than male users. This indicate that male professional out number than female users. Overall findings show that female users are 66% and rest 34% are male users for all four social networks that were analyzed in this research work.